2021
DOI: 10.4155/bio-2020-0256
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Lc–Ms/Ms Method for the Quantification of Toxic Payload Dm1 Cleaved from Bt1718 in a Phase I Study

Abstract: Background: BT1718 is a novel bicyclic peptide anticancer drug targeting membrane type I matrix metalloproteinase to release its toxic payload DM1. A LC–MS/MS method was validated to quantify DM1 generated from BT1718 in a Phase I/IIa clinical trial. Materials & methods: Plasma samples underwent a reduction reaction to artificially cleave BT1718 into DM1 and its bicycle components. An alkylation step was carried out to stabilize the reaction products, and plasma proteins extracted using acetonitrile. LC–MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In 2021, Bicycle Therapeutics (Nasdaq: BCYC) announced three investigational BTC (bicyclic peptide‒toxin coupled) drugs: BT1718, BT5528, and BT8009 36 , 37 , 38 . All in phase I/II clinical development.…”
Section: General Consideration Factor Of Pdc and Clinical Trials Of Pdcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Bicycle Therapeutics (Nasdaq: BCYC) announced three investigational BTC (bicyclic peptide‒toxin coupled) drugs: BT1718, BT5528, and BT8009 36 , 37 , 38 . All in phase I/II clinical development.…”
Section: General Consideration Factor Of Pdc and Clinical Trials Of Pdcsmentioning
confidence: 99%
“… Name TTP Payload Linker Indication Development phase Clinical trials registry Ref. ANG1005 Angiopep-2 Paclitaxel Succinic acid Leptomeningeal metastases Phase III NCT03613181 (2021) 135 , 136 Glioma Glioblastoma brain tumor, recurrent Phase II NCT00539344 (2014) 137 Breast cancer brain metastases Phase II NCT02755987 (2016) 138 NCT01967810 (2020) Advanced solid tumors with and without bain metastases Phase I NCT02048059 (2020) 139 NCT00539383 (2016) GRN1005 Angiopep-2 Paclitaxel Succinic acid Breast cancer brain metastases; non-small cell lung cancer (nsclc) with brain metastases Phase II NCT01480583 (2016) 89 , 140 NCT01497665 (2019) NCT01679743 (2019) BT1718 MT1-MMP binder DM1 Disulfide Advanced solid tumours non-small cell lung cancer non-small cell lung sarcoma oesophageal cancer Phase I/II NCT03486730 (2020) 38 BT5528 EphA2 binder MMAE Amide Solid tumours EphA2-positive NSCLC Phase I NCT04180371 (2021) 36 , 39 , 141 BT8009 Nectin-4 binder MMAE Amide Solid tumors Phase I NCT04561362 (2021) …”
Section: General Consideration Factor Of Pdc and Clinical Trials Of Pdcsmentioning
confidence: 99%
“…Another bicyclic peptide was utilized in the study of Gowland et al for the targeted delivery of mertansine to membrane type I matrix metalloproteinase (MT1-MMP) in an ongoing Phase I/IIa human clinical trial for the treatment of advanced solid tumors ( Figure 17 ). The first phase of this trial demonstrated the superior pharmacokinetic profile of the hybrid ( 54 ), while more data are expected upon completion of the clinical trial [ 136 ].…”
Section: Peptide Hybrids With Natural Productsmentioning
confidence: 99%
“…Due to its low molecular weight and good distribution compared with antibody-drug conjugates, BT1718 may quickly penetrate and 'kill' tumor cells, showing a therapeutic effect on advanced solid tumors. The bicyclic peptide also has other inherent characteristics to minimize drug toxicity, such as short systemic half-life, rapid penetration into tumors, low systemic exposure, and rapid renal clearance [24].…”
Section: Targeting Integrinsmentioning
confidence: 99%